2010
DOI: 10.1210/jc.2009-2032
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Cognitive Impairments in Patients with Long-Term Cure of Cushing’s Disease

Abstract: Cognitive function, reflecting memory and executive functions, is impaired in patients despite long-term cure of Cushing's disease. These observations indicate irreversible effects of previous hypercortisolism on cognitive function and, thus, on the central nervous system. These observations may also be of relevance for patients treated with high-dose exogenous glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 38 publications
5
78
0
1
Order By: Relevance
“…This has already been observed in multiple other medical conditions (24). This relationship is a relevant observation, since patients with longterm cure of CS have persistent complaints reflected in impaired QoL (3)(4)(5). These complaints are often misunderstood and difficult to treat.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This has already been observed in multiple other medical conditions (24). This relationship is a relevant observation, since patients with longterm cure of CS have persistent complaints reflected in impaired QoL (3)(4)(5). These complaints are often misunderstood and difficult to treat.…”
Section: Discussionmentioning
confidence: 74%
“…Following successful treatment of hypercortisolism, signs and symptoms improve substantially. However, prolonged, excessive exposure to glucocorticoids may have long-lasting adverse effects on behavioral and cognitive functions, due to functional and structural alterations in specific brain target areas (1)(2)(3)(4). Furthermore, these patients do not completely return to their premorbid level of functioning, and quality of life (QoL) is persistently impaired despite long-term cure of CS (5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CS is associated with morphological changes of the brain (including brain atrophy, reduction in total and cortical grey matter and reduced hippocampal volume), which at least partially persist after long-term remission (32,33). This may explain the chronic cognitive impairments described in patients in long-term remission of CS (4,34), which may negatively influence QOL. Other explanations for the impaired QOL could be the previous experience of suffering a severe illness, ineffective coping strategies or illness perceptions (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Cushingoid phenotype improves after curative treatment, there is accumulating evidence that not all changes in body composition, cardiovascular risk profile and cognitive function are reversible (2,3,4). Furthermore, a number of studies have reported that quality of life (QOL) remains impaired in patients in long-term remission of CS (5,6,7,8,9,10,11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment might be important to reduce the long-term consequences of hypercortisolism. Indeed, after curing CD, improvement of cardiovascular risk and psychological manifestations is only partial (5,6).…”
Section: Introductionmentioning
confidence: 99%